Leadership and Overtime Incentives: Mental Health and Gen Z Job Satisfaction - Masruroh, Rina; Mariana, Lia; Irawan, Nico; Oktaviani, Winda (IJSM, 2025)
This study aimed to analyze the influence of empowering leadership, overtime work, and overtime incentives on the job satisfaction of Generation Z employees at Kuningan Regency, with employee mental health as a mediating variable. The research was motivated by the fluctuating employee turnover rate over the past three years and increasing challenges in managing Gen Z employees. A quantitative approach was used, employing Structural Equation Modeling (SEM) through AMOS. A total of 156 respondents were selected using purposive sampling. The results showed that empowering leadership did not significantly affect mental health, but had a direct positive effect on job satisfaction. Overtime work had a positive effect on mental health but a negative effect on job satisfaction. Overtime incentives did not significantly affect mental health, but had both direct and indirect positive effects on job satisfaction through mental health. Mental health played a significant mediating role in the relationship between overtime work and overtime incentives with job satisfaction, but not in the relationship between empowering leadership and job satisfaction. The model demonstrated a good level of fit. These findings highlighted the importance of balanced management of overtime and incentives, as well as the critical role of mental health in improving Gen Z employee satisfaction.